Effect of refrigeration systems upon frozen bull sperm viability assessed by computer-assisted sperm analysis and fluorescent probes - Mungai Chacur, Marcelo George; Dias, Huberson Sanches; Papa, Patricia de Mello; Papa, Frederico Ozanam [UNESP]; Melo-Ona, Cely Marini [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Sperm cryopreservation success depends upon the maintenance of spermatozoa fertility potential. Sperm cells must preserve both integrity and functionality of several cell structures. The stabilization phase must allow the exit of water from the sperm cells via osmosis. This study aimed to compare the effect of refrigeration in the commercial refrigerator (CR) and the transport/refrigeration box (TRB) upon the viability of frozen bull sperm diluted in three different extenders (A, B and C). Ten Nellore bulls, Bos taurus indicus maintained in Artificial Insemination Center were used and the spermatozoa samples was assessed for Plasma Membrane Integrity and CASA evaluation. The stabilization phase (5 degrees C/4 hours) was performed in the CR as well as in the TRB, and then samples were exposed to nitrogen vapor during 20 minutes and then plunged into nitrogen. The statistical analysis was done using the variance analysis and the significance level was set at 5%. In the CR the post-thawing parameters for PM and ALH were higher (p < 0.05) in the extender A (glicine egg-yolk) and extender B (glicine egg-free) when compared with extender C (TRIS egg-yolk). As for BCF, STR and LIN, the parameters were higher (p < 0.05) in extender B than in C. Samples that were stabilized in the TRB presented higher post-thawing parameters (p < 0.05) for PM and LIN in extender A and extender B when compared with C. BCF and STR parameters were higher (p < 0.05) in extemder B when compared with C. Extender B samples had higher (p < 0.05) PMI when stabilized in CR. The findings in this experiment enable us to say that both CR and TRB were effective in keeping the viability of post-thawing bull semen.
Keywords: Zebu bull; cooled semen; frozen semen; CASA; membrane integrity